Leadership and Operational Indexes for Supply Chain Resilience - Solis, Maribel Mendoza; García Alcaraz, Jorge Luis; Solórzano, Juan Manuel Madrid; Macías, Emilio Jiménez (SpringerBriefs in Applied Sciences and Technology, 2023)
XVI, 115 p. 25 illus., 9 illus. in color.